Etika Bisnis dan Tanggung Jawab Sosial Rumah Sakit dalam Pengelolaan Dampak Lingkungan: Tinjauan Sistematis - Ahmed, Muhammad; Supriyadi, Supriyadi; Redjeki, Finny; Delima, Mera (Jurnal Akademika Baiturrahim Jambi, 2025)
Hospitals, as healthcare service providers, hold a strategic role in ensuring the quality of care while simultaneously facing challenges as business institutions that must carry moral and social responsibilities. Operational activities, such as medical waste management, energy consumption, and the use of chemicals, have the potential to negatively impact the environment. This study aims to examine the relationship between business ethics and Corporate Social Responsibility (CSR) in hospital management, with the expected output being the identification of implementation strategies that support environmental sustainability. The method employed was a literature review analyzing recent studies related to business ethics, CSR, and environmental management practices in hospitals. The findings indicate that applying ethical values such as honesty, responsibility, fairness, and environmental concern, combined with CSR practices through proper waste management, emission reduction, and community education, strengthens hospitals’ commitment to environmental issues. In conclusion, consistent application of business ethics and CSR not only enhances hospital reputation and public trust but also contributes significantly to sustainable development.